Graphene quantum dots as selective fluorescence sensor for the detection of ascorbic acid and acid phosphatase via Cr(vi)/Cr(iii)-modulated redox reaction. Issue 19 (21st April 2016) - Shi, Fanping; Zhang, Yu; Na, Weidan; Zhang, Xinyang; Li, Yan; Su, Xingguang
Abstract : A facile and rapid fluorescence assay based on a redox reaction for successively detecting ascorbic acid and acid phosphatase was developed via Cr(vi )-modulated graphene quantum dots (GQDs). Abstract : A facile and rapid fluorescence assay based on a redox reaction for successively detecting ascorbic acid and acid phosphatase was developed via Cr(vi )-modulated graphene quantum dots (GQDs). Graphene quantum dots with yellow-green emission were first synthesized via a one-pot hydrothermal method. Based on the electrostatic adsorption of Cr 3+ on GQDs and the strong chelation between Cr 3+ and the –COOH and –OH groups on the surface of GQDs, the fluorescence of GQDs could be greatly quenched by Cr 3+ ions. By the introduction of ascorbic acid, Cr2 O7 2− could be reduced to Cr 3+, which resulted in quenching of the fluorescence signal of GQDs. The degree of quenching of the fluorescence intensity of GQDs was proportional to the concentration of ascorbic acid. The dynamic detection range for ascorbic acid was from 0.5 to 250 μmol L −1 with a limit of detection (LOD) of 0.28 μmol L −1 . Moreover, this phenomenon was further exploited for the sensitive and selective detection of acid phosphatase (ACP).l -Ascorbic acid-2-phosphate (AAP), which is a more stable phosphatase substrate, could be hydrolyzed by ACP to give ascorbic acid. Ascorbic acid then reduced Cr2 O7 2− to Cr 3+, leading to quenching of the fluorescence of GQDs. Thus, the amount of ACP could be indirectly detected in the range from 0.02 to 3 mU mL −1 with a LOD of 8.9 μU mL −1 . Thus, a Cr(vi )-modulated GQDs "turn-off" fluorescence sensor for ascorbic acid and ACP was constructed. The present strategy showed high selectivity for ascorbic acid and ACP. The feasibility of the proposed sensing system in a real sample assay was also studied and satisfactory results were obtained.